Probing the Imortal Universe how the web program series Anino?t Panaginip : the Hidden Chapters of Imortal relates and interacts to the television series IMORTAL - De Guzman, Antonio Luis R. 1987- (2012)
"With the emergence of the Internet as a new medium, a number of media industries and outside of the country began adapting to the change by integrating content to the Internet through digitization. This thesis studies how the web program series Anino't Panaginip: The Hidden Chapters of Imortal, an Internet content primarily create as a part of the larger online brand extension of the television series Imortal--Imortal Universe--which offers textual narratives of the entire Imortal mythology, games, and user-generated content to online consumers, relates and interacts to the television series Imortal in terms of content production, production and distribution. The researcher interviewed the project head, producer, and head writer of the said web program series and juxtaposed their responses with the textual analysis of their web episodes. The study, through the lens of Relational Patterns of Interaction theory, shows that the web series Anino't Panaginip: The Hidden Chapters of Imortal has established a symmetrical relationship to the television series Imortal in terms of content, production, and distribution. Moreover, the study shows that the television, despite the symmetrical relationship established, still manages to be the dominant medium."
Vita.
Undergraduate thesis (A.B. Broadcast Communication)--University of the Philippines, Diliman.
Keywords: Anino't Panaginip : the Hidden Chapters of Imortal; Interactive television -- Philippines; Internet television -- Philippines